Yād-i Ḥālī : yaʻnī vah maz̤āmīn jo jashn-i ṣad sālah yādgār paidāʼish Shamsulʻulamāʼ Ḵẖvājah Alt̤āf Ḥusain ṣāḥib Ḥālī ke mauqiʻ par ʻUs̲māniyah Kālij, Aurangābād meṉ paṛhe gaʼe - Muḥīuddīn (SAMP early 20th-century Indian books project ;)
On the life of Ḵẖvājah Alt̤āf Ḥusain Ḥālī, 1837-1914, Urdu poet; contributed articles.